Readiness Level and Factors Influencing Tourist Decisions to Visit Banjar Hot Springs, Buleleng District in Pandemic Era of Covid-19 - Suryawati, Dewa Ayu; Flaviana Osin, Rosvita (Akademi Komunitas MAPINDO, 2022)
The travel and tourist industry has been severely impacted by the COVID-19 pandemic's onslaught. The significant decline in the number of tourist visits during the Covid-19 pandemic greatly affected the economic conditions of a region. Various efforts have been made by tourism object managers in order to attract tourists to return to visit. This study aims to identify readiness and factors that are considered by tourists visiting the Banjar hot spring tourist attraction in Buleleng Regency. The method used in this research is mixed methods, namely quantitative and qualitative. The number of samples used in this study were 95 people using incidental sampling. Data collection using a questionnaire. Data analysis techniques using factor analysis. The results of the study show that the Banjar hot spring tourism object is ready to face the new normal period by considering various factors. Furthermore, by using the Principal Component Analysis (PCA) method, four (4) factors and 19 variables were obtained that influenced tourists visiting the Banjar hot spring tourist attraction, Buleleng Regency during the Covid-19 pandemic and were able to explain all the variants in the data, namely 72.236%. Keywords : Tourist Attraction, Hot Spring, Tourist